2016
DOI: 10.14348/molcells.2016.0150
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β-Induced RBFOX3 Inhibition Promotes Epithelial-Mesenchymal Transition of Lung Cancer Cells

Abstract: The RNA-binding protein Rbfox3 is a well-known splicing regulator that is used as a marker for post-mitotic neurons in various vertebrate species. Although recent studies indicate a variable expression of Rbfox3 in non-neuronal tissues, including lung tissue, its cellular function in lung cancer remains largely unknown. Here, we report that the number of RBFOX3-positive cells in tumorous lung tissue is lower than that in normal lung tissue. As the transforming growth factor-β (TGF-β) signaling pathway is impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…The TGF-beta signaling pathway is a classical tumorigenesis-related pathway; it exerts dual and opposing roles in oncogenesis, inhibiting cell proliferation in early tumors and inducing tumor progression and metastasis in advanced cancer (Seoane and Gomis, 2017;Batlle and Massague, 2019). Previous studies have shown that RBPs can interact with the TGF-beta signaling pathway to regulate lung carcinogenesis (Kim et al, 2016;Bai et al, 2019). These results suggest that RBPs can affect the growth of tumor cells by regulating multiple biological processes, such as the TGF-beta signaling pathway, RNA metabolism, and RNA processing.…”
Section: Discussionmentioning
confidence: 99%
“…The TGF-beta signaling pathway is a classical tumorigenesis-related pathway; it exerts dual and opposing roles in oncogenesis, inhibiting cell proliferation in early tumors and inducing tumor progression and metastasis in advanced cancer (Seoane and Gomis, 2017;Batlle and Massague, 2019). Previous studies have shown that RBPs can interact with the TGF-beta signaling pathway to regulate lung carcinogenesis (Kim et al, 2016;Bai et al, 2019). These results suggest that RBPs can affect the growth of tumor cells by regulating multiple biological processes, such as the TGF-beta signaling pathway, RNA metabolism, and RNA processing.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies reported RBFOX3 was exclusively expressed in post-mitotic neurons of the central nervous system, recent studies indicated that RBFOX3 is also expressed in some non-neuronal tissues [30, 31]. Another study showed that RBFOX3 expression was inhibited during TGF-β-induced epithelial-mesenchymal transition (EMT) in lung cancer [32]. Nevertheless, the cellular function of RBFOX3 in tumorigenesis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 It was previously shown, that certain cytokines such as IL-6, IL-8 or TGFb initiate and/or sustain the mesenchymal cancer cell state. [36][37][38] We used TGFb to induce EMT in A549 cells, which express low levels of endogenous BOK. When exogenous BOK expression was induced in those cells, TGFbinduced phenotypic change was prevented ( Fig.…”
Section: Molecular Cancer Biologymentioning
confidence: 99%